2020
DOI: 10.1017/cjn.2020.45
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Covert Brain Infarct-Related Cognitive Impairment and Dementia

Abstract: Covert brain infarcts (CBIs) are five times more prevalent than symptomatic brain infarcts. CBIs are associated with cognitive impairment and therefore may be a target for preventing cognitive decline and dementia. This review focuses on strategies for preventing CBI-related cognitive impairment, either by preventing incident or recurrent CBI or by enhancing cognitive reserve. CBIs begin to become prevalent during midlife and are highly prevalent in later life. The distribution of vascular pathologies of CBI d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Most of the research on cognitive reserve has focused on markers that influence the expression of Alzheimer disease pathology in older individuals, with comparatively few studies of cognitive reserve in midlife or of cognitive dysfunction from cerebrovascular pathology. 2 A few studies suggest that the association of white matter hyperintensities (WMH) with lower cognition is attenuated in persons with higher education. 3 However, whether other potential factors modify the degree of cognitive dysfunction in persons with WMH is not known.…”
mentioning
confidence: 99%
“…Most of the research on cognitive reserve has focused on markers that influence the expression of Alzheimer disease pathology in older individuals, with comparatively few studies of cognitive reserve in midlife or of cognitive dysfunction from cerebrovascular pathology. 2 A few studies suggest that the association of white matter hyperintensities (WMH) with lower cognition is attenuated in persons with higher education. 3 However, whether other potential factors modify the degree of cognitive dysfunction in persons with WMH is not known.…”
mentioning
confidence: 99%
“…A limitation of literature on cognitive reserve is that it has mostly been tested in the context of Alzheimer's disease (AD) pathology, where the hypothesis has gained some support [5]. There are few studies on whether cognitive reserve can mitigate the adverse effects of vascular brain pathology, such as white matter hyperintensities (WMHs).…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of literature on cognitive reserve is that it has mostly been tested in the context of Alzheimer’s disease (AD) pathology, where the hypothesis has gained some support. There are few studies on whether cognitive reserve can mitigate the adverse effects of vascular brain pathology, such as white matter hyperintensities (WMHs) [ 5 ]. This is important because vascular pathology is the second biggest contributor to dementia, present in the brain of most persons with AD, mild cognitive impairment (MCI), and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological research showed that silent cerebrovascular disease is five times more prevalent than symptomatic brain infarcts (10) and is associated with future risk for stroke and dementia (11) , thus representing an important opportunity for stroke prevention (1) .…”
Section: Introductionmentioning
confidence: 99%